THE IMPLEMENTATION OF CANTRANG FISHING GEAR PROHIBITION POLICY IN PATI REGENCY - Handayani, Zulaikha Sari; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2020)
ABSTRACT Pati Regency is included in the Java Sea fisheries management area which is currently in an over-exploited condition. The cantrang fishing gear prohibition policy is important to be implemented as an effort to maintain the sustainability of fish resources and ensure the survival of fishermen in Pati Regency. The cantrang fishing gear prohibition policy nowadays is facing implementation delay in Pati Regency. This research aims to analyse the delay implementation of cantrang fishing gear prohibition policy and identify the inhibiting factors of the policy implementation. This research uses a qualitative method with a descriptive approach. The results showed that the implementation of cantrang ban policy in Pati district had been delayed several times, the form of the postponement of the policy are re-verify the size of the cantrang vessel and the issuance of a sailing permit for Cantrang fisherman. The factors that inhibit the policy implememtation are the scope of target group behavior change is difficult to reach, the limited social and economic conditions of target group, low level of apparatus commitmentand the low support from target group. Suggestions that can be given from the results of this research are optimizing the role of the Working Group replacement of tools fishing gear are prohibited to operate, increase the commitment and integrity of the competent personnel by acting strictly on the policy renewal time, granting remission of ship bussiness credit for cantrang fisherman and optimizing the role of POKMASWAS (supervisor community).